The Impact of the Transition to IFRS on Audit Firms in the Saudi Arabia - Alharthi, Sarah Mubarak; Alsaadi, Abdullah Mansour (The Arab Journal of Administration, 2024)
This study aimed to investigate the actual impact of the transition to International Financial Reporting Standards (IFRS) on auditing firms in Saudi Arabia. Specifically, the study sought to analyze the post-IFRS transition reality of auditing firms in Saudi Arabia and to answer the following questions: (i) What is the impact of the transition to IFRS on the types of services provided by auditing firms in Saudi Arabia?; (ii) What is the impact of the transition to IFRS on the resources used by auditing firms in Saudi Arabia (employee experience, number of owners/partners, number of employees with professional certifications, and number of employees in auditing firms)?. To achieve the study’s objectives and answer its questions, the study analyzed auditing firms in Saudi Arabia that audited the accounts and prepared the financial statements of companies listed on the Saudi Stock Exchange during the period 2017-2019. A survey was used to analyze and study the opinions of employees of auditing firms in Saudi Arabia about the impact of the transition to IFRS on auditing firms in Saudi Arabia. An inductive and descriptive analytical approach was used. The study population consisted of employees of auditing firms in Saudi Arabia, who were randomly selected to form a sample of 28 auditing firms operating in Saudi Arabia. The study’s field findings revealed that the transition to IFRS has a positive impact on the following: the types of services provided, employee experience, the number of owners/partners, and the number of employees. The study also found that the transition to IFRS has led to an increase in the demand for auditing services, particularly for complex and specialized services. This is due to the more stringent requirements of IFRS, which require auditors to have a deeper understanding of financial reporting and a broader range of skills. The study concludes that the transition to IFRS has had a positive impact on auditing firms in Saudi Arabia. It has led to an increase in the quality of auditing services, the demand for auditing services, and the resources available to auditing firms.